Nucleolar Dominance in a Tetraploidy Hybrid Lineage Derived From Carassius auratus red var. () × Megalobrama amblycephala () - Cao, Liu; Qin, QinBo; Xiao, Qiong; Yin, HongTing; Wen, Jin; Liu, QiWen; Huang, Xu; Huo, YangYang; Tao, Min; Zhang, Chun; Luo, Kaikun; Liu, ShaoJun (Frontiers in Genetics, 2018)
Nucleolar dominance is related to the expression of 45S rRNA genes inherited from one progenitor due to the silencing of the other progenitor’s rRNA genes. To investigate nucleolar dominance associated with tetraploidization, we analyzed the changes regarding the genetic traits and expression of 45S rRNA genes in tetraploidy hybrid lineage including F1 allotetraploids (4n = 148) and F2 autotetraploids (4n = 200) derived from the distant hybridization of Carassius auratus red var. (2n = 100) (<inline-graphic xlink:href="fgene-09-00386-i003.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />) ×Megalobrama amblycephala (2n = 48) (<inline-graphic xlink:href="fgene-09-00386-i004.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />). Results showed that nucleolar dominance from the females was established in F1 hybrids and it was inherited in F2 hybrids, suggesting that tetraploidization can lead to rapid establishment of nucleolar dominance in the hybrid origin’s tetraploid lineage. These results extend the knowledge of nucleolar dominance in polyploidy hybrid animals, which are of significance for the evolution of hybrids in vertebrates.